Serum C-Reactive Protein/Albumin Ratio in Rheumatoid Arthritis and its Relationship With Disease Activity, Physical Function, and Quality of Life - İsmihan SUNAR and Şebnem ATAMAN (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the relationship between C-reactive protein (CRP)/albumin ratio (CAR) and disease activity, quality of life (QoL), and physical function in rheumatoid arthritis (RA). Patients and methods: A total of 121 RA patients (22 males, 99 females; mean age 57.6±11.2 years; range, 32 to 85 years) applying to Ankara University School of Medicine Rheumatology Outpatient Clinic between January 2019 and February 2019 were included in this cross-sectional study. The inclusion criteria were fulfilling the American College of Rheumatology/European League Against Rheumatism 2010 RA classification criteria, being over 18 years and accepting to participate in the study. Demographic and clinical parameters including serum erythrocyte sedimentation rate (ESR), CRP and albumin levels were recorded. Disease activity was measured using Disease Activity Score 28 (DAS28)-ESR. General health, fatigue, and pain were questioned by means of a 100 mm visual analog scale (VAS). The QoL was assessed with the Rheumatoid Arthritis Quality of Life (RAQoL) Questionnaire. The functional status was determined using the Health Assessment Questionnaire (HAQ). Results: Rheumatoid factor (RF) was positive in 56.2% of the patients. The median ESR was 19.0 mm/hour [interquartile range (IQR): 19.5] and median CRP was 5.6 (IQR: 9) mg/L. The median CAR was 1.3 (IQR: 2.1) and median DAS 28-ESR was 3.6 (IQR: 1.5). There was a significant but weak correlation between CAR and DAS28-ESR [p<0.001, Spearman’s correlation coefficient (rs)=0.327]. Moreover, CAR was positively correlated with ESR, CRP, and VAS physician’s global assessment (p<0.001, rs=0.497; p<0.001, rs=0.987, p<0.001, rs=0.401, respectively). However, no correlation was observed between CAR, HAQ, and RAQoL. In the RF positive group, there was a significant but weak correlation between CAR and RF titers (p=0.016, rs=0.292). Conclusion: We observed a positive but weak correlation between CAR and DAS28-ESR, ESR, and the RF titer. Further studies are warranted to investigate the role of CAR in RA.